Emerging pathogens: the underestimated risk of Kodamaea ohmeri infection in hospitals - Wang, Shuang-Jie; Yu, Xia; Liang, Jia-hui; Zheng, Dong-yan; Cao, Cun-Wei (Frontiers in Microbiology, 2025)
IntroductionKodamaea ohmeri is a rare but significant emerging human pathogen, particularly in neonates, with high mortality rates. While most K. ohmeri infections are sporadic, they can be underestimated during hospital outbreaks owing to challenges with traditional identification methods. We conducted a retrospective study to determine the diagnostic accuracy of detecting K. ohmeri in candidemia.MethodsSix non-duplicated isolates (initially misidentified as Candida dubliniensis) were collected from four patients in a single department over 1 month. Clinical and whole-genome sequencing data of the outbreak strains were evaluated to identify possible outbreaks.ResultsAll patients presented atypical features at diagnosis, and isolates had a low minimum inhibitory concentration (MIC) for amphotericin B, 5-fluorocytosine, and echinocandins, except for fluconazole with a high MIC. Notably, Patient 4 had a high MIC for triazoles. The isolates were grouped into three clades based on core genome single-nucleotide polymorphisms and single-copy orthologous genes. Clade 1 contained isolates from Patients 1 and 2, suggesting a common infection source.ConclusionThis study underscores the need for improved awareness of K. ohmeri infections, which, although rare, involve emerging fluconazole-resistant strains. Kodamaea ohmeri should be considered a potential nosocomial pathogen capable of causing outbreaks; overlooking these emerging human pathogens may have serious consequences.